2011
DOI: 10.1007/s12262-010-0193-2
|View full text |Cite
|
Sign up to set email alerts
|

Role of Prophylactic Antibiotics in Open Inguinal Hernia Repair: A Randomised Study

Abstract: To study the role of prophylactic antibiotics in open inguinal hernia repair. A total of 200 patients were included, they were randomised in two groups. Group 1 was given prophylactic dose of inj amoxy-clav while group 2 was given placebo only. Results were compared and Data analysed using the Chi-square test. Complications in both the groups were compared. Rate of serous discharge and seroma formation was 1% and 22% respectively in group 1 while 2% and 26% in group 2 also the rate of erythema and stitch absce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 11 publications
(9 reference statements)
0
17
0
Order By: Relevance
“…). Of 1683 original studies, 17 RCTs met the inclusion criteria, of which 13 had already been identified and included in previous meta‐analyses; four additional studies were identified, giving a total of 18 eligible RCTs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…). Of 1683 original studies, 17 RCTs met the inclusion criteria, of which 13 had already been identified and included in previous meta‐analyses; four additional studies were identified, giving a total of 18 eligible RCTs.…”
Section: Resultsmentioning
confidence: 99%
“…Characteristics of the 18 RCTs are described in Tables and . Three and 15 trials respectively included herniorrhaphy and hernioplasty (prosthetic mesh). Four antibiotic classes were used in these studies: first‐generation cephalosporins, second‐generation cephalosporins, β‐lactam/β‐lactamase inhibitors and fluoroquinolones.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[8], [19], [20] Recent studies in Indian setting have consistently showed similar incidences of infection in the antibiotics prophylaxis group and control group. [21], [22], [23] However, in one of the studies the incidence of infection in the control group was quiet high.(10.5%). [21] In the recent Cochrane review, which evaluated patients of hernioplasty subgroup, showed that the antibiotic prophylaxis show a significant reduction of wound infection rates.…”
Section: Graphmentioning
confidence: 89%